1991
DOI: 10.1038/bjc.1991.109
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous shunting in patients with colorectal liver metastases

Abstract: SummaryThe outlook for patients with colorectal liver metastases is poor. Microspheres have been combined with cytotoxics and administered via the hepatic artery in an attempt to improve tumour drug exposure within the liver. However, it has been suggested that arteriovenous connections might occur in association with intrahepatic tumours causing loss of regional advantage, and that the administration of microspheres further exacerbates arteriovenous shunting. In seven patients with colorectal liver metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, we have recently shown that base-line shunting in patients with colorectal liver metastases is low and not significantly increased following the regional administration of a 'therapeutic' dose of microspheres (Goldberg et al, 1990b). In clinical practice therefore, we have not found arteriovenous shunting to be a problem.…”
Section: Discussionmentioning
confidence: 75%
“…However, we have recently shown that base-line shunting in patients with colorectal liver metastases is low and not significantly increased following the regional administration of a 'therapeutic' dose of microspheres (Goldberg et al, 1990b). In clinical practice therefore, we have not found arteriovenous shunting to be a problem.…”
Section: Discussionmentioning
confidence: 75%
“…Wheeler et al (1986), in their study of human head and neck cancer, also suggested that some of the shunting they observed (on average 23% of the total blood flow) may have been in normal tissue rather than in the tumour itself. Goldberg et al (1991) have discussed the problems associated with using microspheres for measurement of shunted fraction and concluded that once errors such as leaching of radioactivity from the spheres and heterogeneity in sphere size were minimised the shunted fraction within human liver metastases could be reduced to less than 6%. Gullino and Grantham (1961b), who developed the original method for growing 'tissueisolated' tumours in the ovarian site, used uptake of 42KC1 or 86RbCl and Sapirstein's principles (Sapirstein, 1958) to determine blood flow to rat tumours growing in the ovary for comparison with the total venous outlfow.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of treatment modalities are based on the concept that the metastases receive a predominant hepatic arterial supply1'2. However, some tumours obtain a portal vein supply or establish arterioportal anastomoses [3][4][5][6] in order to compensate for arterial loss in treatment targeting the hepatic artery. These observations growth is dependant on angiogenesis, the process by which new capillary blood vessels are generated from preexisting capillaries and venules, induced by growth factors released by the tumour and from those present in the host milieu8-1.…”
Section: Introductionmentioning
confidence: 99%